Combating the Cult of ISIS: A Social Approach to Countering Violent Extremism. Issue 3 (3rd July 2017) - Day, Joel; Kleinmann, Scott
Abstract : This article argues that status quo Countering Violent Extremism (CVE) programs are rarely based on a theoretically informed understanding of how radical violent mobilization occurs. Examining ISIS radicalization through cult or New Religious Movement (NRM) theory gives practitioners alternative tools for prevention, intervention, and rehabilitation that that rely less on ideology and instead point towards the social processes of extremism, highlighting the importance of affective bonds. Viewing radicalization through the lens of cult-literature means that one can bracket the snares of counter-ideology and instead focus on the affective, social, and organizational ties within the movement. This means that there are potentially factors of radicalization processes that are generalizable to all sorts of extremist violent movements.